The Impact of Multidimensional Curriculum Design in French on Higher-Order Thinking Skills (Critical Thinking, Creative Thinking, and Future Thinking) - Siti Umaya; Asep Herry Hernawan; Laksmi Dewi (Jurnal Pendidikan Indonesia, 2026)
The design of foreign language learning curricula that are integratively capable of fostering students’ higher-order thinking skills remains limited. This study aims to analyze the impact of a multidimensional curriculum in French language instruction on the enhancement of students’ higher-order thinking skills. This research employed a quantitative approach and involved 300 senior high school students and university students. The sample was selected using a purposive sampling technique. A quasi-experimental method was utilized to test a multidimensional curriculum model integrated with critical thinking, creative thinking, and future thinking competencies in the experimental group and to compare the results with those of the control group. The instrument used for data collection was a questionnaire. Data analysis techniques included the independent sample t-test, effect size analysis, and Pearson correlation analysis. The results indicate that higher-order thinking skills in the experimental group improved significantly compared to those in the control group. The dimensions showing the most significant improvement were future thinking and creative thinking, followed by critical thinking. The implementation of foreign language instruction using a multidimensional curriculum can facilitate the development of students’ critical, creative, and future-oriented thinking skills within a relatively short period of time. The multidimensional curriculum model should be supported by innovative and creative instructional strategies or methods that promote higher-order thinking skills among second language learners.